IMPLEMENTASI KEBIJAKAN KARTU IDENTITAS ANAK (KIA) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SAMARINDA - Niningsih, Salasiah, dan Sumarni (Prodi Ilmu Administrasi Negara, 2022)
Therefore, this study aims to find out the implementation of the child identity card(KIA) policy in the Population and Civil Registration Office of Samarinda City and to findout the supporting factors and obstacles in the implementation of the child identity card(KIA) policy in the Population and Civil Registry Office of Samarinda City.This research belongs to a type of descriptive research using a qualitativeapproach which means this research describes a real phenomenon or event. Informants inthis study as many as 7 people as informants. Research data is obtained from various datasources, namely primary data and secondary data. Data collection is done throughobservation, interviews and documentation. Data analysis techniques used are datareduction, data presentation, Conclusion drawing and verification.The results showed that the implementation of the child identity card (KIA) policyin the Population and Civil Registration Office of Samarinda City through 6 indicators,namely: 1) communication, 2) resources, 3) disposition and 4) bureaucratic structureshowed quite well. This can be seen from the socialization and printing of children'sidentity cards carried out directly in elementary schools with competent employees whoadhere to the SOP that has been stipulated in the Samarinda City Regional Regulation.The supporting factor is communication and resources that are going well. While theinhibitory factors are disposition, bureaucratic structure, facilities and infrastructure, aswell as the covid 19 outbreak.